Investigation on the Effects of GLP1 analog and SGLT2 inhibitor against Diabetic Cardiomyopathy in Type 2 Diabetic Rats: Possible Underlying Mechanisms - Abdelaziz M. Hussein; Elsayed A. Eid; Medhat Taha; Rami M. Elshazli; Raouf Fekry Bedir; Lashin Saad Lashin (Highlights on Medicine and Medical Research Vol. 9, 2021)
Background: The present study investigated the possible cardioprotective effects of GLP1 and SGLT2i against diabetic cardiomyopathy (DCM) in type 2 diabetic rats and the possible underlying mechanisms. DCM is defined as the presence of heart failure in absence of coronary artery disease. Methods: Thirty-two male Sprague Dawley rats were randomly subdivided into 4 equal groups; a) control group, b) DM group, type 2 diabetic rats with saline daily for 4 weeks, c) DM+ GLP1, as DM group with GLP1 analogue (liraglutide) at a dose of 75 µg/kg for 4 weeks, and d) DM+ SGLT2i: as DM group with SGLT2 inhibitor (dapagliflozin) at a dose of 1mg/kg for 4 weeks. By the end of treatment (4 weeks), serum blood glucose, HOMA-IR, insulin and cardiac enzymes (LDH, CK-MB) were measured. Also, the cardiac histopathology, myocardial oxidative stress markers (MDA, GSH and CAT) and norepinephrine (NE), myocardial fibrosis, the expression of caspase-3, TGF-\(β\), TNF-\(α\) and tyrosine hydroxylase (TH) in myocardial tissues were measured. Results: T2DM caused significant increase in serum glucose, HOMA-IR, serum CK-MB and LDH (p< 0.05). Also, DM caused significant myocardial damage and fibrosis, elevation of myocardial MDA, NE with upregulation of myocardial caspase-3, TNF-\(α\), TGF-\(β\) and TH and significant decrease in serum insulin and myocardial GSH and CAT (p<0.05). Administration of either GLP1 analog and SGLT2i caused in significant improvement in all studied parameters (p< 0.05). Conclusion: We concluded that either of GLP1 and SGLT2i exhibited cardioprotective effects against DCM in T2DM with the upper hand for SGLT2i. This might be due to attenuation of fibrosis, oxidative stress, apoptosis (caspase-3), sympathetic nerve activity and inflammatory cytokines (TNF-\(α\) and TGF-\(β\)).